2008
DOI: 10.1103/physreva.77.043420
|View full text |Cite
|
Sign up to set email alerts
|

Nonsequential two-photon double ionization of helium

Abstract: We present accurate time-dependent ab initio calculations on fully differential and total integrated (generalized) cross sections for the nonsequential two-photon double ionization of helium at photon energies from 40 to 54 eV. Our computational method is based on the solution of the time-dependent Schroedinger equation and subsequent projection of the wave function onto Coulomb waves. We compare our results with other recent calculations and discuss the emerging similarities and differences. We investigate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
308
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(345 citation statements)
references
References 48 publications
35
308
2
Order By: Relevance
“…Provided one of the electrons is emitted perpendicular to the laser polarization direction, it is found that the angular distribution of the other electron is characterized by three lobes. The results are similar to those recently reported for the corresponding process in the hydrogen negative ion [R. The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Provided one of the electrons is emitted perpendicular to the laser polarization direction, it is found that the angular distribution of the other electron is characterized by three lobes. The results are similar to those recently reported for the corresponding process in the hydrogen negative ion [R. The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
supporting
confidence: 73%
“…The problem of direct (nonsequential) two-photon double ionization of helium has been studied extensively in recent years, as exemplified by numerous theoretical [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and experimental [19][20][21][22][23][24] works. This breakup process is fundamental in the sense that it is one of the simplest processes in nature where electron correlations are exhibited, manifested by a rather complex interplay between the electrons.…”
mentioning
confidence: 99%
“…2. TPDI, which would be distributed along the lines parallel to the second diagonal [64,65], cannot be observed in the spectrum. ) second SDI steps are presented in Fig.…”
Section: Sequential Tpdi Of Ne At 44 Ev: a Kinematically Complete Expmentioning
confidence: 99%
“…5. According to a series of calculations [51,56,57,[63][64][65]68,101], a change of the shape of the energy distribution between both electrons should be expected. As discussed, e.g., in [63], for the photon energies of 40-45 eV equal energy sharing between both emitted electrons is needed in order to overcome the attraction of the nucleus and promote both electrons into the continuum (see Fig.…”
Section: Recoil Ion Momentum Distributions For Double Ionization Of Hmentioning
confidence: 99%
“…One can use among others MC-HF [12], Hylleraas-type variational or coupled spherical harmonics calculations. We used the results of [13] especially adapted to our radial grid. The reconstruction schematically works in the following way:…”
Section: Application To Helium Excitation Spectrummentioning
confidence: 99%